Food culture in medieval Scandinavia - Gyönki, Viktória; Maraschi, Andrea (Early medieval North Atlantic., 2022)
The making, eating, and sharing of food throughout society represents an important and exciting area of study with the potential to advance the field of scholarship, particularly in the context of Scandinavian Studies. This book analyses the historical, legal, and literary sources of the region during the medieval period to explore different aspects of Scandinavian culture relating to food and drink: production, consumption (including feasts), trading (distribution), and the associated social rituals. Using new and innovative approaches, this collection of studies offers broad insights into a great variety of social practices and includes fresh information on not only social history but also traditional topics such as trade, commercial exchange, legal regulation, and political organisation. The book unites contributors from a variety of backgrounds, further enriching the content of a collection that promises to make a significant contribution to the state of current research.